Research on the progress of regional ecological security evaluation and optimization of its common limitations - Jiafeng Wen (Elsevier, 2021)
Ecological security evaluation research is a crucial part of ecological sustainable development. Scientific evaluation is conducive to the rational allocation of regional ecological resources and accurately predicts of the development trend of ecological security. Recently, ecological security evaluation mainly focuses on two directions: one is quantitative and qualitative research on the concentration and distribution characteristics of pollutants in ecological regions; the other is the construction of ecological security evaluation model and the application of evaluation methods. Based on the current research status in terms of index system construction, evaluation methods, weight setting, etc., it is concluded that the common limitations of current ecological security evaluation research mainly focused on the unclear division of ecological security level thresholds, inconsistent evaluation index systems, and determination of ecological security driving forces. It also discussed the optimization feasibility of these common constraints in aspects such as coupling with the evaluation results and the prediction and verification. The research results could enrich the discussion of common problems that need to be solved in ecological security evaluation, provide feasible ideas for the further development of ecological security evaluation research, and provide theoretical reference value for some specific problems in practical evaluation.